Geography, location, and strategy - Silverman, Brian S.; Alcácer, Juan; Kogut, Bruce Mitchel; Thomas, Catherine, active 2017; Yeung, Bernard Yin (Advances in strategic management ;, 2017)
Changes in both technology and global political economy have vastly accelerated the pace of globalization in the last 40 years, eroding barriers that limited firms' geographic scope, and unleashing a seemingly unlimited set of new threats, challenges, and opportunities to create value globally. Globalization presents managers with an environment to create value that is more complex, risky, and also more promising than ever before. Despite recent advances in our understanding of how locations impact the creation and appropriation of value by firms, the speed of these changes has often surpassed the speed of research on the connections between geography and firms. This volume draws together researchers working at the forefront of this area in a variety of disciplines-economics, geography, marketing, organizational behavior, psychology, sociology, and strategy - in order to explore the many ways that locations matter for firms. In 11 varied papers, the authors draw on newly available data, recently developed theory, and diverse methodology to understand the relationships between firm boundaries, firm activities, and geographic borders.